Procalcitonin as a diagnostic marker for infection in sickle cell disease. Issue 6 (3rd June 2022) - Maharaj, Satish; Chang, Simone
ABSTRACT: Background: Patients with sickle cell disease (SCD) are at increased risks of infection. Fever often occurs with vaso-occlusive crisis (VOC), posing a diagnostic challenge in SCD. Procalcitonin (PCT) is an infectious biomarker validated in the general population but with limited data on use in SCD. Methods: We performed a retrospective single-center study (n = 145) with primary objective of assessing ability of PCT to differentiate infection from VOC in SCD presenting with fever. Subgroups included confirmed bacterial infection (CBI), suspected bacterial infection, viral infection, and VOC. A secondary objective examined the association of PCT with acute chest syndrome. Clinical characteristics and data were collected and analyzed to assess the diagnostic performance of PCT and associated variables. Results:   Of the cohort, 16% had CBI and 8% had viral infection. PCT was able to discriminate CBI from viral infection [AUC = 0.89 (95%CI, 0.78–0.99)] and VOC [AUC = 0.87 (95%CI, 0.78–0.97)]. PCT had an association with ACS but poor diagnostic performance [AUC = 0.69 (95% CI, 0.54–0.84)]. Conclusion: PCT has utility in distinguishing confirmed bacterial infection from VOC or viral infection and is a promising biomarker when investigating fever in SCD.